The Pneumatologi Pentakostal sebagai Lensa Hermeneutik bagi Teologi Allah Trinitas - Pranoto, Minggus Minarto (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2025)
This article aims to explain the theology of the Triune God from the perspective of Pentecostal theology. The hermeneutical key for exploring this theme begins with believers’ experience of the person and work of the Holy Spirit, which is inseparable from the work of the other two persons of the Trinity. This experience serves as the basis for critically and theologically examining and reflecting on the theology of the Triune God. The method employed in this article is an exploration of key teachings in Pentecostalism, such as pneumatological hermeneutics, the doctrine of the Full Gospel, and Spirit baptism, in order to explain the theology of the Triune God. Furthermore, the distinctive features of these teachings are brought into dialogue with selected biblical narratives, Patristic theology, and systematic theology in order to strengthen the teaching on the Triune God within Pentecostalism. The author’s thesis is that Pentecostal theology can uniquely contribute to the articulation of the theology of the Triune God through pneumatological hermeneutics, the doctrine of the Full Gospel, and the doctrine of Spirit baptism.